Projected Performance of an InxGa1-xAs Quantum Dot Intermediate Band Solar Cell - Amin, Sayeda Anika; Hasan, Md. Tanvir (AIUB Journal of Science and Engineering (AJSE), 2017)
Quantum Dot Intermediate Band Solar Cell (QDIBSC) is one of the emerging technologies in the solar photovoltaic arena, which has immense potential to be demonstrated as a high efficiency device. For a QDIBSC to surpass the efficiency of a single junction cell, optimization of design is required. In this work, a QDIBSC model based on In0.53Ga0.47As quantum dots has been designed and evaluated with respect to dot size and spacing. The impact of carrier lifetime on short-circuit current and open-circuit voltage is studied. The conversion efficiency has been enhanced from 27.1% to 32.62% as compared to a conventional single junction cell.